The characteristic symphony in the age of Haydn and Beethoven - Will, Richard James (New perspectives in music history and criticism., 2002)
'Characteristic' symphonies have texts associating them with literature, politics, religion, and other aspects of eighteenth- and early nineteenth-century European culture. This first full-length study of the genre illuminates the relationship between symphonies and their aesthetic and social context and discusses examples of works by composers including Beethoven, Haydn and Dittersdorf.